Integrating Technology in Mathematics Education: A Research Synthesis of Learning Outcomes and Pedagogical Implications - Amaludin, Roni; Akib, Irwan; Sukmawati, Sukmawati (PPSDP International Journal of Education, 2025)
The integration of digital technologies is transforming mathematics education, yet empirical findings on its impact remain varied. This research synthesis examines the effects of technology integration on learning outcomes and pedagogical practices. A systematic search of the Scopus database was conducted for peer-reviewed articles published between 2020 and 2024 using keywords such as “technology integration,” “digital learning,” and “mathematics education.” The synthesis of 20 studies indicates that tools like GeoGebra, Augmented Reality (AR), and Artificial Intelligence (AI) enhance conceptual understanding, student engagement, and personalized learning. Furthermore, pedagogical approaches like Realistic Mathematics Education (RME) and Flipped Learning, when combined with technology, foster active and student-centered environments. The critical role of teacher digital competence (TPACK) was a consistent theme. While technology shows significant benefits, future efforts must address equitable access, develop effective feedback mechanisms, and explore culturally adaptive AI applications to ensure inclusive and sustainable integration.